Method Development, Validation and Forced Degradation Studies For the Determination of Moxifloxacin in Bulk and Pharmaceutical Dosage Forms Using UV Spectroscopy - Aruna, E.; Sri, K. Bhavya; Sumakanth, M. (Asian Journal of Pharmaceutical Research and Development, 2021)
The objective of this work was to develop and validate spectrophotometric method for moxifloxacin for analysis. A very simple, unique, novel, reliable and easy method of spectrophotometric estimation in UV-region has been developed for the assay of moxifloxacin tablet formulation and also to perform forced degradation studies. Method: water was used as diluents to perform all the validation parameters and stress studies. Results: ICH guidelines were adopted during the method development and the method was validated statistically by calculating RSD and %RSD. The drug obeys Beer’s lamberts law at 1-10 mcg/ml concentration. Accuracy, Linearity, precision and robustness LOD at 3.3 ppb levels, LOQ at 11.2 ppb levels was performed. % of drug Degradations at different parameters were determined. Conclusion: - This method can be used for the routine laboratory analysis and can extend the studies to chromatographic techniques.